Spousal associations between social participation and chronic diseases among Chinese middle-aged and older adults: an actor-partner interdependence model analysis - Ruan, Yunchen; Li, Yan; Wang, Qingbao (Frontiers in Public Health, 2025)
ObjectivesWhile previous studies have explored the link between a spouse’s social participation and their partner’s general physical health among Chinese middle-aged and older adults, none have examined its association with partner chronic disease or potential gender differences. Our study aims to address this gap.MethodsThis study used data from the 2013, 2015, and 2018 waves of the China Health and Retirement Longitudinal Study (CHARLS). The sample comprised 3,072 couples where both partners were aged 45 or older. Chronic disease was defined as the count of self-reported chronic conditions. Social participation was measured as the number of distinct social activity types engaged in. Analyses employed the actor-partner interdependence model (APIM).ResultsSpousal social participation was significantly associated with partner chronic disease, with significant gender differences. Specifically, the wife’s social participation was positively associated with the husband’s chronic diseases, whereas the husband’s social participation was negatively associated with the wife’s chronic diseases. Furthermore, the wife’s depressive symptoms significantly mediated both of these associations.ConclusionSpousal social participation is associated with partner chronic disease among Chinese middle-aged and older adults, with the nature of this association varying significantly by gender. These findings suggest that developing and strengthening social support networks, alongside implementing gender-sensitive interventions to promote social participation, could improve health outcomes.